Deep Blue: Discovering the Sea - Caroline Shackleton; Nathan Paul Turner (NewYork Cambridge University Press, 2014)
Discover the many mysteries of the sea - shipwrecks and sunken treasure, deep sea creatures and mythical monsters - and how people explore this amazing place.